Etnomatematika: arsitektur masjid raden anji ma’ra sebagai media pembelajaran - Saparwadi, Lalu; los Santos, Maria Clara de; Soberano, Liza (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Purpose: This study aims to analyze ethno-mathematical concepts within the architecture of the Raden Anji Ma’ra Great Mosque in Lombok to address student difficulties in mathematics by providing contextual learning media. Design/methodology/approach: This qualitative ethnographic study utilizes the researcher as the primary instrument. Data were gathered through structural observations, photographic documentation, and literature reviews of local architecture. Findings: The results reveal various plane geometry concepts (rectangles, triangles, circles) and solid geometry (spheres, cylinders, prisms) within the mosque's elements. Findings also encompass principles of symmetry, geometric transformations, and architectural proportions rich in mathematical value. Practical implications: These findings provide teachers with culturally-relevant alternative teaching materials to enhance students' interest and conceptual understanding through concrete objects in their surroundings.Originality/value: This study offers a unique contribution by exploring mosque architecture in Lombok, which has remained largely unexamined in ethno-mathematics literature, thereby expanding the integration of socio-religious culture into mathematics education. Purpose: Penelitian ini bertujuan menganalisis konsep etnomatematika pada arsitektur Masjid Jamik Raden Anji Ma’ra Lombok untuk mengatasi kesulitan siswa dalam memahami matematika melalui penyediaan media pembelajaran kontekstual. Design/methodology/approach: Studi kualitatif etnografi ini menggunakan peneliti sebagai instrumen utama. Data dikumpulkan melalui observasi struktur bangunan, dokumentasi foto, dan studi literatur mengenai arsitektur lokal. Findings: Hasil penelitian mengungkap keberadaan konsep geometri bidang (persegi panjang, segitiga, lingkaran) dan geometri ruang (bola, tabung, prisma) pada elemen masjid. Temuan juga mencakup prinsip simetri, transformasi geometri, dan proporsi arsitektural yang kaya akan nilai matematis. Practical implications: Temuan ini menyediakan bahan ajar alternatif berbasis budaya lokal bagi guru untuk meningkatkan minat dan pemahaman konseptual siswa melalui objek konkret di lingkungan sekitar. Originality/value: Studi ini memberikan kontribusi unik dengan mengeksplorasi arsitektur masjid di Lombok yang selama ini belum terjamah dalam literatur etnomatematika, memperluas cakrawala integrasi budaya-agama dalam pendidikan matematika.